Types and archetypes in Motýl's variation on a medieval theme. - Hrtánek, Petr (Bohemica Olomucensia, 2023)
This article deals with the novel by Petr Motýl Příběh pana rytíře Vítka a jeho dcery Anežky (The Story of Knight Vítek and his daughter Anežka, 2020). It focuses on types of characters and archetypal motifs, using Northrop Frye's concept of mythoi, i. e. narrative plots (comedy, romance, tragedy, satire) connected with seasons and vegetation cycles. It is reflected in subgenre metamorphoses of Petr Motýl's historical fiction.
Keywords: Petr Motýl; historical fiction; types of characters; archetypal motifs; mythos